The assessment of planned preventive maintenance of residential estates of the district hospital in the Sekyere-West District of the Ashanti Region - Asiseh, Vincent Korsi (Jnr) (2011)
A thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of MSc.degree in Health Services Planning and Management.